The Effect of Job Stress on Employee Performance at the Departement of Maritime Affairs and Fisheries of North Sumatera Province - Sihombing, Herbet P; Oktaviani, Annisa (Yana Research, 2024)
The success rate of performance will be good if work stress can be overcome because work stress is fundamental because it plays a role in reducing the quality and quantity of work. The purpose of this study was to determine and analyze the effect of work stress on performance. This research was conducted at the Department of Maritime Affairs and Fisheries of North Sumatra Province with a total sample of 130 employees. Data were obtained from work stress scales and performance, using survey methods, which were processed using simple regression analysis methods. This study uses an adaptation scale, where the scale has been used or examined by previous researchers. However there are aitems that are canceled after an online trial. through google form to 100 subjects. Based on the hypothesis obtained that work stress affects performance at the Department of Maritime Affairs and Fisheries of North Sumatra Province this can be seen from the significance value of 0.000 or <0.05.